Multidimensional GC using planar microfluidic devices for the characterization of phenolic antioxidants in fuels. Issue 17 (26th July 2013) - Luong, Jim; Gras, Ronda; Cortes, Hernan J.; Shellie, Robert A.; Svec, Frantisek
<x xml:space="preserve">Abstract</x> A multidimensional gas chromatographic approach using planar microfluidic devices for Deans switching has been developed and implemented for the characterization of sterically hindered phenolic compounds used as antioxidants in fuels. Detection and quantitation was conducted with MS in selected ion monitoring mode. A complete analysis is conducted in less than 15 min with precision greater than 5.5% at 1 and 25 ppm w/w (ppmw). LODs of 50 ppb w/w (ppbw) or better in selected ion monitoring mode and a linear range of 100 ppbw to 100 ppmw with a correlation coefficient greater than 0.998 were attained for all analytes. Unique to this analytical configuration is the use of a mass spectrometer capable of monitoring the column effluent from either dimension by incorporating a high‐temperature rotary valve and a three‐port planar microfluidic device. High‐molecular‐weight (C25–C40) fuel contaminants eluting from the first column can be selectively sent to the mass spectrometer for profile characterization in scan mode. These compounds would otherwise be retained substantially by the low‐phase‐ratio analytical column employed in the second dimension.